Expression of CUEDC2 in colorectal cancer with different invasion and migration abilities. Issue 2 (February 2019) - Hu, Shidong; Hu, Zilong; Li, Songyan; He, Changzheng; Wu, Youjun; Teng, Da; Yan, Yang; Li, Hao; Xing, Xiaowei; Zou, Guijun; Li, Yuxuan; Yang, Yu; et al.
Objective: To investigate CUE domain containing 2 ( CUEDC2 ) expression in colorectal cancer with different invasion and migration abilities. Methods: Fresh colon cancer tissues, obtained from patients with or without lymph node metastasis who were treated at the Department of General Surgery, Chinese People's Liberation Army General Hospital, and SW620 and HT29 colorectal cancer cell lines, were analysed for CUEDC2 expression. Results: Real-time polymerase chain reaction showed significantly higher CUEDC2 mRNA levels in colon cancer tissue from patients with ( n = 8) versus without ( n = 8) lymph node metastasis, and in SW620 versus HT29 cells. Western blots revealed significantly higher CUEDC2 protein levels in colon cancer tissues from patients with versus without lymph node metastasis, and in SW620 versus HT29 cells. Colorectal cancer tissues from patients with lymph node metastasis showed more intense immunohistochemical staining and moderate staining of cell nuclei and cytoplasm versus less intense/weak staining in tissues from patients without lymph node metastasis. Conclusions: CUEDC2 is highly expressed in colorectal cancer tissues and colorectal cancer cell lines with high invasion and migration ability. CUEDC2 may be involved in promoting invasion and metastasis in colorectal cancer.